Суммаро ҳисоб кунед:
\(1\cdot2+2\cdot3+...+(n-1)\cdot n\)
\(C_n=1\cdot2+2\cdot3+...+(n-1)\cdot n\)
\(S_n=1+2+...+n\)
\(C_n=(2+3+...+n)+(3+4+...+n)+...+(n-1+n)+n=\)
\(=(S_n-S_1)+(S_n-S_2)+...+(S_n-S_{n-1})=\)
\(=(n-1)\cdot S_n-(S_1+S_2+...+S_{n-2}+S_{n-1})\)
\(S_n=\frac{1}{2}n(n+1)=\frac{1}{2}(n^2+n)\)
\((n-1)\cdot S_n=(n-1)\cdot(\frac{1}{2}(n^2+n))=\frac{1}{2}(n-1)(n^2+n)\)
\(C_n=\frac{1}{2}(n-1)(n^2+n)-\frac{1}{2}(1^2+1+2^+2+...+(n-1)^2+(n-1))=\)
\(=\frac{1}{2}(n-1)(n^2+n)-\frac{1}{2}(1^2+2^2+...+(n-1)^2+1+2+...+(n-1))\)
\(1^2+2^2+...+k^2=\frac{1}{6}n(n+1)(2n+1)\)
\(C_n=\frac{1}{2}(n-1)(n^2+n)-\frac{1}{2}(\frac{1}{6}n(n+1)(2n+1)+\frac{1}{2}(n-1)n)=\)
\(=\frac{1}{2}(n-1)(n^2+n-\frac{2n^n-n}{6}-(\frac{n}{2}))=\)
\(=\frac{(n-1)(6n^2+6n-2n^2+n-3n)}{12}=\frac{(n-1)(4n^2+4n)}{12}=\)
\(=\frac{4(n-1)(n^2+n)}{12}=\frac{n(n-1)(n+1)}{3}=\frac{n(n^2-1)}{3}\)
\((a-b)(a+b)=a^2-b^2\)
\((n-1)(n+1)=n^2-1^2=n^2-1\)
Ҷавоб: \(\frac{n(n^2-1)}{3}\)